1983
DOI: 10.1152/ajpendo.1983.244.5.e459
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid metabolism in the ovine fetus

Abstract: Quantitative measurements of the umbilical uptake of a variety of substrates were made in the ovine fetus in both the fed state and after 5 days of maternal fasting. Blood flow was measured in both study periods using the antipyrine method, with the simultaneous measurement of umbilical vein and arterial concentrations of glucose, oxygen, and 25 amino acids in whole blood. Umbilical blood flow and fetal oxygen consumption remained unchanged between the fed and fasted states. Umbilical glucose uptake decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 17 publications
2
53
0
1
Order By: Relevance
“…This suggests that serine and glycine have unique fetal metabolic characteristics when compared with their metabolism in the adult. These same studies in fetal sheep have shown a negligible uterine uptake of glycine but a large umbilic al release of glycine from the placenta to the fetus (20,21), and the converse for serine, a measurable net uterine uptake with no measurable release of this amino acid from the placenta to the fetus in both the mid-and late-gestation fetus (7,22,23). Ther efore, there is no apparent transfer of serine from the mother to the fetus.…”
Section: ---------------------mentioning
confidence: 91%
“…This suggests that serine and glycine have unique fetal metabolic characteristics when compared with their metabolism in the adult. These same studies in fetal sheep have shown a negligible uterine uptake of glycine but a large umbilic al release of glycine from the placenta to the fetus (20,21), and the converse for serine, a measurable net uterine uptake with no measurable release of this amino acid from the placenta to the fetus in both the mid-and late-gestation fetus (7,22,23). Ther efore, there is no apparent transfer of serine from the mother to the fetus.…”
Section: ---------------------mentioning
confidence: 91%
“…In this study, the naturally occurring opioid peptides, leu-enkephalin, dynorphin A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and the synthetic peptides, DADLE, TIPP and TIPP-ψ, were incubated with the BeWo cell monolayers at 37°C. The surface area of a 12-well plate used in the metabolism study was larger than the surface area of Side-Bi-Side diffusion unit, and the degradation of the naturally occurring peptides became significant.…”
Section: Stability Of Opioid Peptides Upon Exposure To Bewo Cell Monomentioning
confidence: 99%
“…Although passive diffusion is the principal mechanism of transport across the placenta (9), several carrier-mediated transport mechanisms (e.g. for glucose, fatty acids and amino acids) have been identified (10,11). Several in vivo and in vitro models have been utilized to study the transport of substances across the placental barrier (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Over this period the partitioning of available energy between growth and oxidation remains constant, but there is a 37% decline in energy requirements per kg fetal tissue ( Table 1). Despite the magnitude of these changes in fetal metabolism, as long as maternal metabolism or placental function are not compromised the energy requirements for fetal maintenance and growth are met in equal parts by fetal uptake of glucose and amino acids (Lemons & Schreiner, 1983 9 Lemons & Schreiner (1983).…”
Section: Fetal-placental Interactionsmentioning
confidence: 99%
“…Glucose uptake can decrease by up to 30% following a 5 d period of starvation in late-gestation sheep (Lemons & Schreiner, 1983). Amino acid uptake remains unchanged but much greater proportions of amino acids are oxidized and this leads to a doubling in urea-N production.…”
Section: Maternal Nutrition and Fetal Growthmentioning
confidence: 99%